“A Deplorable Speech”: The Liberal Party vs. Anti-Catholicism during the Alexander Mackenzie Administration, 1873–1878 - Forbes, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2017)
After decades of raising the “no popery” cry and fighting for the strict separation of church and state, Canada’s Liberal Party leaders began in the 1870s to distance themselves from their previous reputation for anti-Catholicism and from their hardline approach to church-state policy. This article examines the Alexander Mackenzie administration’s response to the Argenteuil Speech of 1875, in which Liberal cabinet minister Lucius Huntington called for all Protestants to unite with liberal Catholics to challenge the Roman Catholic Church’s rising political influence in Canada. Although several prominent Protestants applauded the speech, and Prime Minister Mackenzie himself privately admitted his agreement, the administration publicly condemned the speech as anti-Catholic and effectively crushed Huntington’s vision for the party. By forcing the party leaders to choose between their historic principles and their broader electoral appeal, Huntington’s “deplorable speech” facilitated a turning point in the Liberal Party’s approach to religious matters.